The Effect of Business Competition on Sales Volume at Vegetable Traders in the Pasar Minggu, Pandan Jaya Village - Abidin, Zaenal; Nurjali; Ulfa, Siti Maria (Zabags International Journal of Economy, 2025)
One of the places where business activities take place is the market. The market is a place where buyers and sellers gather and interact through various products or certain types of products. Competition provides benefits for entrepreneurs and consumers. Because with competition, entrepreneurs will try to continue to improve the quality of the products or services they offer. This encourages them to continue to innovate and strive to provide the best products or services to consumers. This study aims to determine whether there is a significant impact of the influence of business competition on sales volume at vegetable traders in the weekly market, Pandan Jaya sub-district. This research method uses a descriptive quantitative type, namely research that emphasizes its analysis on numerical data (numbers) which are processed with a statistical model using a simple linear regression equation Y = a + bX. The number of samples in this study was 35 respondents, namely vegetable traders in the weekly market, Pandan Jaya sub-district. The results of this study state that business competition has a significant effect on sales volume at vegetable traders. We can see this from Tcount = 2,350 and Ttable = 1,995 with a significant value of 0.0108 <0.05, which means that Ho is rejected and Ha is accepted, which means that business competition in Pandan Jaya sub-district has a positive and significant effect on sales volume at vegetable traders.